The Mononuclear Phagocyte System in Organ Transplantation. Issue 4 (28th January 2016) - Ochando, J.; Kwan, W.‐H.; Ginhoux, F.; Hutchinson, J. A.; Hashimoto, D.; Collin, M.
Abstract : The mononuclear phagocyte system (MPS) comprises monocytes, macrophages and dendritic cells (DCs). Over the past few decades, classification of the cells of the MPS has generated considerable controversy. Recent studies into the origin, developmental requirements and function of MPS cells are beginning to solve this problem in an objective manner. Using high‐resolution genetic analyses and fate‐mapping studies, three main mononuclear phagocyte lineages have been defined, namely, macrophage populations established during embryogenesis, monocyte‐derived cells that develop during adult life and DCs. These subsets and their diverse subsets have specialized functions that are largely conserved between species, justifying the introduction of a new, universal scheme of nomenclature and providing the framework for therapeutic manipulation of immune responses in the clinic. In this review, we have commented on the implications of this novel MPS classification in solid organ transplantation. Abstract : The authors review the implications of a novel mononuclear phagocyte system nomenclature in solid organ transplantation and provide the phenotypic characterization to distinguish its multiple subsets.